Continuity of care interventions for people with stroke and their caregivers: A scoping review protocol - Meera Premnazeer; Sarah E. P. Munce; Mark T. Bayley; Kristina M. Kokorelias; Monique Gill; Orianna L. Scali; Jill I. Cameron (PLoS ONE, 2025)
Background The needs of people with stroke and caregivers’ change as they transition across the stroke care continuum from initial symptom onset to community living. Continuity of care interventions may support these changing needs. Continuity of care refers to care provided to individuals that is coherent, connected, and consistent across settings. Interventions have been developed to enhance continuity of care, but to date, no reviews have identified the core components of these interventions specific to various care transitions. Objective To examine the literature on continuity of care interventions that address the needs of people with stroke and/or their caregivers specific to stroke care transitions. Methods The study is guided by the Joanna Briggs Institute methodological framework for scoping reviews. The search will be conducted on Ovid MEDLINE, CINAHL Plus with Full Text, PsycINFO, and EMBASE, restricting to articles in English. Core concepts of stroke (e.g., ischemic or hemorrhagic stroke) and continuity of care (e.g., early supported discharge) and their synonyms will be used as search terms. Two reviewers will assess articles for inclusion. Data will be extracted and synthesised using quantitative descriptive analysis and deductive content analysis. A steering committee, consisting of people with lived experiences, researchers, and healthcare professionals, will discuss the charted data, and identify any gaps in the literature. Discussion This research will identify the components of continuity of care interventions, the specific transitions that they address, and any variability in components across different transitions. This research will identify gaps in the continuity of care literature such as where transition interventions are needed.